Kebijakan Hukum Pidana Dalam Perlindungan Terhadap Korban Perkosaan - Marcelus Moses Parera (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this research is to find out the policy of rape victim protection in Indonesian positive criminal law, the prospect of regulating / formulating the protection of rape victims in the national criminal law in the future. The method used is the normative juridical approach used to reveal legal rules and norms which are Podana's legal policies in formulating protection for victims of rape, the sociological approach always tests the empirical validity of a regulation or legal statement that is appropriate or not in accordance with a particular society, in this case in the rape case. The criminal process in this case contains a general and concrete meaning, the prospect of protection of victims of rape in future criminal law, namely by the inclusion of a criminal penalty for damages into an additional criminal sanction so that the judge can impose it simultaneously with the main criminal or independently if the offense concerned only punishable by a single fine. Protection of victims of crime is associated with one of the objectives of punishment, namely resolving conflicts